AN APPROACH TO CREATIVE SPEAKING ACTIVITIES (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract. The main objective of initial foreign language instruction centers on fostering oral proficiency. In the process of learning a foreign language, speaking typically involves reproduction and imitation, with activities geared towards generating precise output with close support. However, achieving fluency and fundamental speaking abilities requires more than simply regurgitating memorized language chunks. In essence, to advance in acquiring the target language and to attain genuine communicative competence, learners must also demonstrate the ability to use language spontaneously and creatively. This article suggests an approach to enhance discursive skills in the advancement of oral communication.